Hydraulic ex situ through-plane characterization of porous transport layers in PEM water electrolysis cells. (1st February 2018) - Bromberger, Kolja; Ghinaiya, Jagdishkumar; Lickert, Thomas; Fallisch, Arne; Smolinka, Tom
Abstract: This paper describes new methods to characterize the hydraulic behavior of porous transport layers (PTL) by using capillary flow porometry (CFP). We present the standard procedure of CFP to gain access to the biggest pore, the mean flow pore and the smallest pore size as well as the absolute through-plane gas permeability of PTLs. An extended method is introduced to measure the relation of capillary pressure versus liquid saturation. It is shown that capillary pressure has a significant influence on mass transport limitation (MTL) in PEM electrolysis cells using a flow field. Furthermore, a new method is proposed to measure the intrinsic contact angle of PTLs by using water and a reference liquid with a contact angle of zero. It is shown that knowing the pore size distribution and the contact angle is essential for studying the influence on capillary pressure. In the course of this study results of CFP are compared to results from mercury porosimetry. We prove that the contact angle is strongly influenced by the titanium oxide layer which forms during electrolysis operation due to electrochemical oxidation of titanium. In summary, we propose a simple key parameter that describes the ability of partially saturated PTLs to transport gas in through-plane direction, termed gas transportability. The latter is introduced and employed to analyze polarization curves of different PTLs. Highlights: Measuring method is proposed to determine capillarity of PTLs. Measuring method is proposed to determine mean intrinsic contact angle of PTLs. Gas transportability is introduced to describe gas transport through PTLs. Contact angle of water is strongly influenced by the TiO2 layer in the PTL. Capillarity of PTL has a significant influence on mass transport limitation.